An Approach for a Personal Information Management System for Photos of a Lifetime by Exploiting Semantics - Khalid, Latif; Mustofa, Khabib; A Min, Tjoa (Springer Berlin Heidelberg, 2006)
Photo collections are one of the promising sources to tell story of life in this digital era. In this paper we present our work on organizing photos of a lifetime by exploiting semantic annotations. The complexity in using semantic technology is managed by introducing an annotation template corresponding to who, when, where, and what. Semantics of each dimension are semi-automatically annotated following the ontology for personal information. The story telling is done by exploiting these semantics to form trails of the photos. The notion of landmarks is used for this purpose which also ensures effective navigation in the lifetime photo-space.